الانتخابات البرلمانية الليبية الأولى سنة 1952بين قوانين التنظيم والتجربة الديمقراطية - محمد الزرقاء سالم (Al-Qurtas, 2025)
الانتخابات البرلمانية الليبية الأولى سنة 1952بين قوانين التنظيم والتجربة الديمقراطية